The Problematic Development of the Stalking Protection Order. Issue 2 (14th January 2020) - Kelly, Rory
Abstract: In 2019, Parliament enacted the Stalking Protection Act. The Act introduces the stalking protection order (SPO); a civil measure the breach of which is an offence. The role of courts in assessing whether similar behaviour orders are penalties has attracted significant scholarly attention. This article examines instead the roles of Government and Parliament in developing the stalking protection order. My central contention is that the Home Office undertook a problematic consultation and the issues to which it gave rise were not addressed in later parliamentary debates. The result was the enactment of a coercive measure of unclear purpose and questionable efficacy. Assessing the roles of the executive and legislature in developing the SPO also allows for fresh insight into wider discussions of behaviour orders. Specifically, I question the language of 'prevention' that is ever‐present in such discussions and describe an important development for debates on whether behaviour orders are penalties.